2009
DOI: 10.1063/1.3153979
|View full text |Cite
|
Sign up to set email alerts
|

Recombination at textured silicon surfaces passivated with silicon dioxide

Abstract: The surfaces of solar cells are often textured to increase their capacity to absorb light. This optical benefit is partially offset, however, by an increase in carrier recombination at or near the textured surface. A review of past work shows that the additional recombination invoked by a textured surface varies greatly from one experiment to another. For example, in the most commonly investigated structure-pyramidal textured silicon diffused with phosphorus and passivated with a hydrogenated oxide-recombinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 40 publications
(69 reference statements)
7
57
0
Order By: Relevance
“…It is worth mentioning that an increase of surface recombination will particularly affect the performance of devices based on active materials with high surface recombination velocity such as single crystalline silicon, GaAs, etc. [ 34,[40][41][42] Furthermore, while nanostructures can increase the overall optical absorption of solar energy harvesting devices, it is important to evaluate how much light absorption enhancement is contributed by the active material as opposed to the passive materials in the device, such as electrodes, since only photocarriers generated in the active light absorber can contribute to the photo-current. Parasitic absorption occurring in the electrodes can cancel out the optical absorption enhancement introduced by nanostructure photon management.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that an increase of surface recombination will particularly affect the performance of devices based on active materials with high surface recombination velocity such as single crystalline silicon, GaAs, etc. [ 34,[40][41][42] Furthermore, while nanostructures can increase the overall optical absorption of solar energy harvesting devices, it is important to evaluate how much light absorption enhancement is contributed by the active material as opposed to the passive materials in the device, such as electrodes, since only photocarriers generated in the active light absorber can contribute to the photo-current. Parasitic absorption occurring in the electrodes can cancel out the optical absorption enhancement introduced by nanostructure photon management.…”
Section: Introductionmentioning
confidence: 99%
“…To sum up the results of the review [105], a 2 -12 times higher recombination is found for lightly doped or non-diffused samples passivated by silicon oxide. This is by far higher than the surface enlargement alone.…”
Section: General Considerations -A Review Of Studies On Alkaline Etchmentioning
confidence: 99%
“…A review on this topic was conducted by McIntosh and Johnson [105]. In terms of surface recombination velocities on non-diffused passivated samples, they report on a wide range of measured values by different groups.…”
Section: General Considerations -A Review Of Studies On Alkaline Etchmentioning
confidence: 99%
“…The wet-chemistry-based approach where solar cells are textured with tetrahedral pyramids having four (111) planes is presently the state-of-the-art in surface texturing. 7,9 This process heavily relies on toxic alkaline solutions. However, in the near future, dry, plasma-based approaches are expected to become more favorable for thinner silicon wafers.…”
Section: Introductionmentioning
confidence: 99%
“…The Scanning Electron Microscopy (SEM) images of the wet-and drytextured Si surfaces are shown in Figure 1. However, due to the fact that the textured surface area is 1.73 times larger than the flat surface and the exposed surfaces are (111) oriented, [7][8][9] the surface passivation becomes more challenging. The reason is the existence of a large number of dangling bonds at the surface.…”
Section: Introductionmentioning
confidence: 99%